The influence of green innovation, eco-efficiency, and environmental costs on company value - Siti Rachellia Imani; Munasiron Miftah (PT WIM Solusi Prima, 2026)
This study aims to empirically determine and analyze how green innovation, eco-efficiency, and environmental costs can affect firm value. This study uses a quantitative method of secondary data in the form of basic material sub-sector manufacturing companies in 2021-2023 that have conducted an initial public offering (IPO) and listed on the Indonesia Stock Exchange. This study uses purposive sampling techniques in selecting samples and uses data regression analysis in conducting data analysis using STATA 17 with significance level of 5%. The results of this study indicate that green innovation has a positive effect on firm value and eco-efficiency has a negative effect on firm value. Meanwhile, environmental costs have no impact on firm value.